The Definition of Witness in Canonical Criminal Procedure and Polish Criminal Procedure - Natalia Grochowska (Kościół i Prawo, 2018)
The aim of this article was to show both similarities and differences in defining a witness in canonical criminal proceedings as well as in Polish criminal procedure. The witness’s testimony is one of the most frequently used types of evidence in both kinds of proceedings. It is also one of the most important sources of evidence in these legal orders. The concept of witness, his rights and obligations and individual categories of witnesses in Polish criminal proceedings and under canon law are not identical. Moreover, the 1983 Code of Canon Law does not provide for specific forms of interrogation, such as: identity parade or interrogation during an inspection or experiment, as is the case in the Polish Code of Criminal Procedure.